Estimating Consumer Inertia in Repeated Choices of Smartphones - Lukasz Grzybowski; Ambre Nicolle (The Journal of Industrial Economics, 2021)
For a sample of 9,799 subscribers to a single mobile operator, we observe switching between mobile handsets between July, 2011, and December, 2014. We estimate a discrete choice model in which we account for disutility from switching to different operating systems and brands. Our estimation results indicate the presence of significant inertia in the choice of operating systems and brands. We use our model to simulate market shares in the absence of switching costs and conclude that the market shares of Android and smaller operating systems would increase at the expense of the market share of iOS in such a context.
Keywords: 330